Cerebrospinal fluid viral escape in aviremic HIV-infected patients receiving antiretroviral therapy: prevalence, risk factors and neurocognitive effects. (1st March 2019) - Pérez-Valero, Ignacio; Ellis, Ronald; Heaton, Robert; Deutsch, Reena; Franklin, Donald; Clifford, David B.; Collier, Ann; Gelman, Benjamin; Marra, Christina; McCutchan, John Allen; Navis, Allison; Sacktor, Ned; et al.
Abstract : Background: During antiretroviral therapy, HIV RNA can be detected in cerebrospinal fluid (CSF) when it is undetectable in plasma, a condition termed 'CSF viral escape'. The aim of the current study was to determine the prevalence and risk factors for CSF viral escape in two large cohorts in the USA. Methods: A total of 1264 HIV-infected volunteers enrolled in two US cohorts at their most recent visit between 2003 and 2011 were included in this cross-sectional analysis if their HIV RNA level in plasma was less than 50 copies/ml while receiving stable antiretroviral therapy (ART) (>6 months) and if they had HIV RNA measured in CSF at their most recent visit between 2003 and 2011. Potential risk factors were identified using univariable and multivariable regression. Results: CSF viral escape was detected in 55 adults (4.4%; 95% CI: 3.4–5.6), who had a median CSF HIV RNA of 155 copies/ml [interquartile range (IQR: 80–283)]. Patients with or without CSF viral escape had similar rates of neurocognitive impairment (38.2 vs. 37.7%; P  = 0.91). CSF viral escape was independently associated with the use of ritonavir-boosted protease inhibitors [odds ratio (OR): 2.0; 95% CI: 1.1–3.8] or unboosted atazanavir (OR: 5.1; 95% CI: 1.3–16.1), CSF pleocytosis (OR: 7.6; 95% CI: 4.2–13.7) and abnormal CSF total protein (OR: 2.1; 95% CI: 1.1–3.7). Conclusions: In this large study of aviremic patients receiving ART, CSF viral escape was uncommon and was linked to evidence of central nervous system inflammation and the use of protease inhibitors, but not with worse neurocognitive performance.